A review of natural hydrofractures in rocks - Bons, Paul D.; Cao, Dongsheng; De Riese, Tamara; Gonzalez-Esvertit, Eloi; Köhn, Daniel; Naaman, Isaac; Sachau, Till; Tian, He; Gomez-Rivas, Enrique (Geological Magazine, 2022)
Hydrofractures, or hydraulic fractures, are fractures where a significantly elevated fluid pressure played a role in their formation. Natural hydrofractures are abundant in rocks and are often preserved as magmatic dykes or sills, and mineral-filled fractures or mineral veins. However, we focus on the formation and evolution of non-igneous hydrofractures. Here we review the basic theory of the role of fluid pressure in rock failure, showing that both Terzaghi's and Biot's theories can be reconciled if the appropriate boundary conditions are considered. We next discuss the propagation of hydrofractures after initial failure, where networks of hydrofractures may form or hydrofractures may ascend through the crust as mobile hydrofractures. As fractures can form as a result of both tectonic stresses and an elevated fluid pressure, we address the question of how to ascertain whether a fracture is a hydrofracture. We argue that extensional or dilational fractures that formed below c. 2-3 km depth are, under normal circumstances, hydrofractures, but at shallower depth they may, but must not be hydrofractures. Since veins and breccias are often the products of hydrofractures that are left in the geological record, we discuss these and critically assess which vein structures can, and which do not necessarily, indicate hydrofracturing. Hydrofracturing can suddenly and locally change the permeability in a rock by providing new fluid pathways. This can lead to highly dynamic self-organization of crustal-scale fluid flow.
CRIS-Team WoS Importer:2023-01-20

Does stress transmission in forelands depend on structural style? Distinctive stress magnitudes during Sevier thin-skinned and Laramide thick-skinned layer-parallel shortening in the Bighorn Basin (USA) revealed by stylolite and calcite twinning paleopiezometry - Beaudoin, Nicolas; Lacombe, Olivier; David, Marie-Eleonore; Köhn, Daniel (Terra Nova, 2020)
The Sheep Mountain-Little Sheep Mountain Anticlines, Bighorn Basin (USA) formed as basement-cored Laramide structures in the formerly undeformed foreland of the thin-skinned Sevier orogen. We take advantage of the well-constrained microstructural network there to reconstruct differential stress magnitudes that prevailed during both Sevier and Laramide layer-parallel shortening (LPS), before the onset of large-scale folding. Differential stress magnitudes determined from tectonic stylolites are compared and combined to previous stress estimates from calcite twinning paleopiezometry in the same formations. During stress loading related to LPS, differential stress magnitudes transmitted from the distant Sevier thin-skinned orogen into the sedimentary cover of the Bighorn basin (11-43 MPa) are higher than the differential stress magnitudes accompanying the early stage of LPS related to the thick-skinned Laramide deformation (2-19 MPa). This study illustrates that the tectonic style of an orogen affects the transmission of early orogenic stress into the stable continental interior.
CRIS-Team WoS Importer:2020-02-14

Evolving geometries, topologies, and apertures in fracture networks: Quantitative insights from lattice modeling - Mathur, Bakul; Prabhakaran, Rahul; Köhn, Daniel (Forces in Mechanics, 2023)
Fracture networks are crucial in controlling rock mass permeability. Some of the important features of the fracture networks like the density, interconnectivity, spatial distribution, and fracture apertures determine the success of the subsurface operations. Fracture networks can be studied with analogue studies, physical experiments, and numerical modeling. In this study, we analyse the evolution of a two-dimensional fracture network under gravitational and shear loads using the lattice modeling capabilities of the microstructural modeling environment “Elle”. The simulation cases include varying gravitational loads and Young's moduli of the formations. The topological progression of the modeled fracture network from isolated to interconnected nodes depicts a realistic network evolution process. The study shows that the rock stiffness exhibits a direct correlation with the number of fractures influencing the average aperture size of the network. A higher gravity load resulted in the development of a sparse fracture network. Stiffer rock models also showed an early onset of fracturing.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Aperture; Elle; Fracture; Lattice; Network

Fracturing and Porosity Channeling in Fluid Overpressure Zones in the Shallow Earth's Crust - Köhn, Daniel; Piazolo, Sandra; Sachau, Till; Toussaint, Renaud (Geofluids, 2020)
At the time of energy transition, it is important to be able to predict the effects of fluid overpressures in different geological scenarios as these can lead to the development of hydrofractures and dilating high-porosity zones. In order to develop an understanding of the complexity of the resulting effective stress fields, fracture and failure patterns, and potential fluid drainage, we study the process with a dynamic hydromechanical numerical model. The model simulates the evolution of fluid pressure buildup, fracturing, and the dynamic interaction between solid and fluid. Three different scenarios are explored: fluid pressure buildup in a sedimentary basin, in a vertical zone, and in a horizontal layer that may be partly offset by a fault. Our results show that the geometry of the area where fluid pressure is successively increased has a first-order control on the developing pattern of porosity changes, on fracturing, and on the absolute fluid pressures that sustained without failure. If the fluid overpressure develops in the whole model, the effective differential and mean stress approach zero and the vertical and horizontal effective principal stresses flip in orientation. The resulting fractures develop under high lithostatic fluid overpressure and are aligned semihorizontally, and consequently, a hydraulic breccia forms. If the area of high fluid pressure buildup is confined in a vertical zone, the effective mean stress decreases while the differential stress remains almost constant and failure takes place in extensional and shear modes at a much lower fluid overpressure. A horizontal fluid pressurized layer that is offset shows a complex system of effective stress evolution with the layer fracturing initially at the location of the offset followed by hydraulic breccia development within the layer. All simulations show a phase transition in the porosity where an initially random porosity reduces its symmetry and forms a static porosity wave with an internal dilating zone and the presence of dynamic porosity channels within this zone. Our results show that patterns of fractures, hence fluid release, that form due to high fluid overpressures can only be successfully predicted if the geometry of the geological system is known, including the fluid overpressure source and the position of seals and faults that offset source layers and seals.
CRIS-Team WoS Importer:2020-08-07

How fluid-mediated rock transformations can mimic hydro-fracturing patterns in hydrothermal dolomite - Centrella, Stephen; Beaudoin, Nicolas E.; Köhn, Daniel; Motte, Geoffrey; Hoareau, Guilhem; Callot, Jean Paul (Marine and Petroleum Geology, 2022)
Numerous studies of hydrothermal dolomite bodies describe brecciated rocks characterized by dark angular fragments of dolomicrite bounded together by saddle dolomite crystals forming veins. Often associated with ore deposits, these hydrothermal dolomite breccia (HDB) patterns are usually interpreted as related to hydro-fracturing and so are considered as univocal markers of fluid overpressure. In this contribution we report an occurrence of typical HDB pattern in a dolomitized sedimentary breccia related to Mesozoic hyper-extension located in the Northern Pyrenees (France). We propose a model that accounts for the textural and crystallographic patterns of a HDB, without any fluid overpressure. The following observations lead us to propose that this HDB results from texturally controlled, hydrothermal fluid-initiated recrystallization of the initial sedimentary breccia by grain boundary migration: (1) the occurrence of rough contacts between the dolomite crystals and an initial dolomitized sedimentary breccia structure; (2) the crystallographic pattern of the hydrothermal dolomite; (3) the different grain size distribution in HDB texture and initial breccia structure; (4) the spatial distribution of oxide particles. Our alternate interpretation was further tested by 2D numerical simulations of the replacement process using the ‘ELLE’ modelling toolbox. Simulations confirm that advection of hot fluids along porous zones can locally trigger recrystallization by grain boundary migration, a replacement of the initial breccia texture and a preservation of larger, less permeable and cold fragments. We propose key features in textural evidence to assess whether HDB texture is pinpointing towards episodes of fluid overpressure and fracturing in carbonates, or if it rather is related to fluid-mediated rock recrystallization.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Breccia; Dolomite; Hydrothermal; Modelling; Recrystallization

Outcrop scale mixing enhanced by permeability variations: the role of stationary and travelling waves of high saturation indices - Köhn, Daniel; Kelka, Ulrich; Toussaint, Renaud; Siegel, Coralie; Mullen, Gary; Boyce, Adrian; Piazolo, Sandra (Geological Magazine, 2022)
To study the ore mineralization at the outcrop scale we merge an advection-diffusion simulation with the geochemical software iphreeqc to model the mixing of two realistic fluids. We simulate the infiltration of a metal-rich fluid into a rock that is saturated with pore fluid. We test the feedback effects with a number of scenarios based on an outcrop-scale 5 x 5 m model consisting of two high-permeable vertical faults within a low-permeable host rock that lead into a permeable layer. The hot metal-rich fluid enters the model through the faults from below. We solve the advection-diffusion equation for 12 chemical species and temperature, and use iphreeqc to determine the resulting properties of local fluid domains as well as related saturation indices for minerals. The faults in the model act as pathways for the metal-rich fluid, with the infiltrating fluid displacing the pore fluid. Mixing in the model takes place as a function of advection along permeable faults coupled with diffusion of chemical species at the interface between two fluids, while heat diffusion is fast enough (10(3) times faster) to equilibrate temperature. Simulations show a high saturation index of mixing-derived minerals such as barite at the interface between the two fluids as a result of fluid mixing. Fast fluid pathways (i.e. faults) show travelling waves of high saturation indices of barite, while low-permeability zones such as fault walls and areas below less permeable layers experience stationary waves of high saturation indices. Our results show that, depending on the dominant transport process (advection or diffusion), mineralization will localize next to permeability contrasts in zones where local diffusion dominates.
CRIS-Team WoS Importer:2022-11-11

Paleogene initiation of the Western Branch of the East African Rift: The uplift history of the Rwenzori Mountains, Western Uganda - Jess, Scott; Köhn, Daniel; Fox, Matthew; Enkelmann, Eva; Sachau, Till; Aanyu, Kevin (Earth and Planetary Science Letters, 2020)
The two branches of the East African Rift System (EARS) are believed to have initiated diachronously. However, a growing body of work continues to suggest the onset of rifting in the Western Branch occurred in the Paleogene, coeval to the Eastern Branch. Due to a lack of pre-Miocene stratigraphy, attempts to resolve the geological history of the Western Branch must study the uplift and erosional histories of the modern rift topography. In this study, the rock uplift history of the Rwenzori Mountains, Western Uganda, is resolved to better our understanding of the tectonic history of the Western Branch of the EAR. Through the application of low-temperature thermochronology, χ-mapping and the modelling of river profiles, we show that rock uplift of the Rwenzori dates back to the Oligocene, with thermal history models suggesting uplift induced exhumation may date back as far as the Eocene. This provides tangible evidence that extension began in the region in the Paleogene, coeval with the Eastern Branch, and not the late Neogene. These results have broad implications for the tectonic evolution of the entire East African Rift System and suggest our current understanding of the region's rift history remains incomplete.
CRIS-Team Scopus Importer:2020-10-09
Keywords: East African Rift; rifting; river profile; thermochronology; uplift; Western Branch

Reconstruction of cyclic Mesozoic-Cenozoic stress development in SE Germany using fault-slip and stylolite inversion - Köhler, Saskia; Duschl, Florian; Fazlikhani, Hamed; Köhn, Daniel; Stephan, Tobias; Stollhofen, Harald (Geological Magazine, 2022)
The Franconian Platform of SE Germany and the underlying Permian and Triassic rocks that developed from latest Permian to Triassic time were affected by multiple compressional and extensional events that created a complex fracture, fault and stylolite network. We reconstructed the spatio-temporal variations of post-Triassic palaeostress fields in the Franconian Platform and Triassic strata using fault-slip and tectonic stylolite inversion. Our highly resolved stress inversion enables us to demonstrate a cyclic stress evolution from the stress regime of normal faulting to thrusting, strike-slip and back to normal faulting. Five main stress fields correlating with two stress cycles are determined for Late Jurassic to Cenozoic time. The first cycle consists of: (SF1) an initially NE-SW-directed horizontal extension during Late Jurassic to Early Cretaceous time; (SF2) NNE-SSW-directed horizontal compression with an early set of tectonic stylolites prior to the development of reverse and thrust faults; and (SF3) a strike-slip-dominated setting with (N)NE-(S)SW horizontal compression representing a first relaxation. The second cycle comprises (SF4) NW-SE-directed horizontal extension during Oligocene-Miocene time; and (SF5) a second strike-slip-dominated regime with WNW-ESE to NW-SE horizontal compression during the Alpine shortening, creating the youngest set of tectonic stylolites. In addition, we consider the transitional stages between thrusting and a strike-slip regime as a snapshot in the process of intraplate tectonics.
CRIS-Team WoS Importer:2022-08-26

Reconstruction of the Temperature Conditions of Burial-Related Pressure Solution by Clumped Isotopes Validates the Analysis of Sedimentary Stylolites Roughness as a Reliable Depth Gauge - Beaudoin, Nicolas E.; Köhn, Daniel; Aharonov, Einat; Billi, Andrea; Daeron, Matthieu; Boyce, Adrian (Minerals, 2025)
Rough surfaces known as stylolites are common geological features that are developed by pressure solution, especially in carbonate rocks, where they are used as strain markers and as stress gauges. As applications are developing in various geological settings, questions arise regarding the uncertainties associated with quantitative estimates of paleostress using stylolite roughness. This contribution reports for the first time a measurement of the temperature at which pressure solution was active by applying clumped isotopes thermometry to calcite cement found in jogs linking the tips of the stylolites. This authigenic calcite formed as a redistribution of the surrounding dissolved material by the same dissolution processes that formed the extensive stylolite network. We compare the depth derived from these temperatures to the depth calculated from the vertical stress inversion of a bedding parallel stylolite population documented on a slab of the Calcare Massiccio formation (early Jurassic) formerly collected in the Umbria-Marches Arcuate Ridge (Northern Apennines, Italy). We further validate the coevality between the jog development and the pressure solution by simulating the stress field around the stylolite tip. Calcite clumped isotopes constrain crystallization to temperatures between 35 and 40 °C from a common fluid with a δ18O signature around −1.3‰ SMOW. Additional δ18O isotopes on numerous jogs allows the range of precipitation temperature to be extended to from 25 to 53 °C, corresponding to a depth range of 650 to 1900 m. This may be directly compared to the results of stylolite roughness inversion for stress, which predict a range of vertical stress from 14 to 46 MPa, corresponding to depths from 400 to 2000 m. The overall correlation between these two independent depth estimates suggests that sedimentary stylolites can reliably be used as a depth gauge, independently of the thermal gradient. Beyond the method validation, our study also reveals some mechanisms of pressure solution and the associated p,T conditions favouring their development in carbonates.
CRIS-Team Scopus Importer:2025-02-14
Keywords: clumped isotopes; depth modelling; paleopiezometry; stylolites

Regional-scale paleofluid system across the Tuscan Nappe-Umbria-Marche Apennine Ridge (northern Apennines) as revealed by mesostructural and isotopic analyses of stylolite-vein networks - Beaudoin, Nicolas E.; Labeur, Aurelie; Lacombe, Olivier; Köhn, Daniel; Billi, Andrea; Hoareau, Guilhem; Boyce, Adrian; John, Cedric M.; Marchegiano, Marta; Roberts, Nick M.; Millar, Ian L.; Claverie, Fanny; et al. (Solid Earth, 2020)
We report the results of a multiproxy study that combines structural analysis of a fracture-stylolite network and isotopic characterization of calcite vein cements and/or fault coating. Together with new paleopiezometric and radiometric constraints on burial evolution and deformation timing, these results provide a first-order picture of the regional fluid systems and pathways that were present during the main stages of contraction in the Tuscan Nappe and Umbria-Marche Apennine Ridge (northern Apennines). We reconstruct four steps of deformation at the scale of the belt: burial-related stylolitization, Apenninic-related layer-parallel shortening with a contraction trending NE-SW, local extension related to folding, and late-stage fold tightening under a contraction still striking NE-SW. We combine the paleopiezometric inversion of the roughness of sedimentary stylolites - that constrains the range of burial depth of strata prior to layer-parallel shortening - with burial models and U-Pb absolute dating of fault coatings in order to determine the timing of development of mesostructures. In the western part of the ridge, layer-parallel shortening started in Langhian time (similar to 15 Ma), and then folding started at Tortonian time (similar to 8 Ma); late-stage fold tightening started by the early Pliocene (similar to 5 Ma) and likely lasted until recent/modern extension occurred (similar to 3 Ma onward). The textural and geochemical (delta O-18, delta C-13, Delta 47CO2 and Sr-87/Sr-86) study of calcite vein cements and fault coatings reveals that most of the fluids involved in the belt during deformation either are local or flowed laterally from the same reservoir. However, the western edge of the ridge recorded pulses of eastward migration of hydrothermal fluids (>140 degrees C), driven by the tectonic contraction and by the difference in structural style of the subsurface between the eastern Tuscan Nappe and the Umbria-Marche Apennine Ridge.
CRIS-Team WoS Importer:2020-09-25

Relationship between stylolite morphology and the sealing potential of stylolite-bearing carbonate cap rocks - Wu, Jun; Fan, Tailiang; Gomez-Rivas, Enrique; Cao, Qian; Travé, Anna; Gao, Zhiqian; Kang, Zhihong; Köhn, Daniel; Bons, Paul D. (Geological Society of America Bulletin, 2023)
We analyzed the sealing effectiveness of cap rocks bearing different types of stylolites using a combination of petrographic, petrophysical, pore structure, and sealing capacity characterization techniques. This study was based on examples of carbonate cap rocks that seal ultradeep hydrocarbon reservoirs of the Tarim Basin (China). Samples from both drill cores and their outcrop analogues were investigated to quantify how morphology influences the sealing capacity of different types of stylolite-bearing rocks. The study cap rocks consisted of mudstone, wackestone to packstone, grainstone, and dolomitic limestone. Four types of stylolites were identified: rectangular layer, seismogram pinning, suture and sharp peak, and simple wave-like types. The difference in the sealing capacity of carbonate cap rocks is attributed to their pore structure connections and the types of stylolites they develop. Samples bearing simple wave-like stylolites showed the best sealing capacity, followed by those with rectangular layer and suture and sharp peak types, whereas carbonates hosting seismogram pinning types had the lowest sealing capacity. The impact of stylolite segments on the rock sealing properties, however, differed from one segment to another. Rectangular layer–type stylolites could be divided into three distinct segments (with good, moderate, and poor sealing, respectively). Both the seismogram pinning and suture and sharp peak stylolite types were divided in two parts, with the former one having moderate and poor sealing and the latter exhibiting good and moderate sealing. The simple wavelike type had a good sealing capacity all along the pressure-solution seam. The most effective sealing barriers for vertical fluid flow form when (1) calcite and siliceous cements are pervasively distributed in the vicinity of stylolites, forming highly cemented zones with lower porosity and permeability than their surrounding host rocks; (2) stylolites are enriched in insoluble residues; and (3) rare microfractures and dissolution vugs are found along the stylolites. This work provides useful examples for the prediction of the sealing potential of stylolite-bearing carbonate rocks according to stylolite morphology in other geologic settings.
CRIS-Team Scopus Importer:2023-03-31

Relative rates of fluid advection, elemental diffusion and replacement govern reaction front patterns - Köhn, Daniel; Piazolo, Sandra; Beaudoin, Nicolas E.; Kelka, Ulrich; Spruženiece, Liene; Putnis, Christine V.; Toussaint, Renaud (Earth and Planetary Science Letters, 2021)
Replacement reactions during fluid infiltration into porous media, rocks and buildings are known to have important implications for reservoir development, ore formation as well as weathering. Natural observations and experiments have shown that in such systems the shape of reaction fronts can vary significantly ranging from smooth, rough to highly irregular. It remains unclear what process-related knowledge can be derived from these reaction front patterns. In this contribution we show a numerical approach to test the effect of relative rates of advection, diffusion, and reaction on the development of reaction fronts patterns in granular aggregates with permeable grain boundaries. The numerical model takes (i) fluid infiltration along permeable grain boundaries, (ii) reactions and (iii) elemental diffusion into account. We monitor the change in element concentration within the fluid, while reactions occur at a pre-defined rate as a function of the local fluid concentration. In non-dimensional phase space using Péclet and Damköhler numbers, results show that there are no rough fronts without advection (Péclet<70) nor if the reaction is too fast (Damköhler>10−3). As advection becomes more dominant and reaction slower, roughness develops across several grains with a full microstructure mimicking replacement in the most extreme cases. The reaction front patterns show an increase in roughness with increasing Péclet number from Péclet 10 to 100 but then a decrease in roughness towards higher Péclet numbers controlled by the Damköhler number. Our results indicate that reaction rates are crucial for pattern formation and that the shape of reaction fronts is only partly due to the underlying transport mechanism.
CRIS-Team Scopus Importer:2021-05-07
Keywords: advection; diffusion; grain boundary network; reaction front; replacement; roughness

Scaling analysis, correlation length and compaction estimates of natural and simulated stylolites - Köhn, Daniel; Köhler, S.; Toussaint, R.; Ghani, I.; Stollhofen, Harald (Journal of Structural Geology, 2022)
Stylolites are rough dissolution surfaces that show three different scaling regimes in space and time. On the small scale surface energy dominates and stylolites roughen very slowly with a growth exponent of about 0.5 and a roughness exponent of about 1.0. On the intermediate scale elastic energy dominates and the surfaces roughening is happening faster with a growth exponent of about 0.8 and a roughness exponent of about 0.5. The transitional length between these two scaling regimes is determined by the stress during stylolite growth and termed as cross-over length scale. On the large scale another transition is reached beyond which the stylolite amplitude remains constant, this length scale is termed the correlation length. The correlation length is determined by time of growth or by the amount of compaction that happened at the interface as well as by the stylolite's system size. This length scale grows as a function of time and the dynamic exponent, which is about 2 in the surface energy dominated regime and 0.625 in the elastic energy dominated regime. We present examples of these scaling regimes for numerical as well as natural stylolites and show how the exponents can be used to determine the stylolite compaction through the different regimes. The numerical stylolites show an increase of correlation length as a function of system size in self-affine time series. Large samples of natural tectonic stylolites from Jurassic limestones of the Franconian Alb (SE Germany) exhibit all three scaling regimes in a self-affine space series. The important length scales in the natural system are the grain size or noise at 30 μm, the cross-over length between the surface and elastic energy dominated regimes at 1.4 mm and the correlation length at 5.7 cm. The overall compaction on the tectonic stylolite is estimated to be in the range of 8 cm.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Compaction; Correlation length; Roughness; Scaling; Stylolites

Simulating Hydraulic Fracturing: Failure in Soft Versus Hard Rocks - Aleksans, Janis; Köhn, Daniel; Toussaint, R.; Daniel, G. (Pure and Applied Geophysics, 2019)
In this contribution we discuss the dynamic development of hydraulic fractures, their evolution and the resulting seismicity during fluid injection in a coupled numerical model. The model describes coupling between a solid that can fracture dynamically and a compressible fluid that can push back at the rock and open fractures. With a series of numerical simulations we show how the fracture pattern and seismicity change depending on changes in depth, injection rate, Young’s Modulus and breaking strength. Our simulations indicate that the Young’s Modulus has the largest influence on the fracture dynamics and the related seismicity. Simulations of rocks with a Young’s modulus smaller than 10 GPa show dominant mode I failure and a growth of fracture aperture with a decrease in Young’s modulus. Simulations of rocks with a Young’s modulus higher than 10 GPa show fractures with a constant aperture and fracture growth that is mainly governed by a growth in crack length and an increasing amount of mode II failure. These results are very important for the prediction of fracture dynamics and seismicity during fluid injection, especially since we see a transition from one failure regime to another at around 10 GPa, a Young’s modulus that lies in the middle of possible values for natural shale rocks.
CRIS-Team Scopus Importer:2019-12-17
Keywords: Hydrofracturing; microseismicity; numerical modelling; Young’s modulus

Stylolites and stylolite networks as primary controls on the geometry and distribution of carbonate diagenetic alterations - Gomez-Rivas, Enrique; Martin-Martin, Juan Diego; Bons, Paul D.; Köhn, Daniel; Griera, Albert; Trave, Anna; Llorens, Maria-Gema; Humphrey, Elliot; Neilson, Joyce (Marine and Petroleum Geology, 2022)
There is ongoing debate on whether stylolites act as barriers, conduits, or play no role in fluid transport. This problem can be tackled by examining the spatial and temporal relationships between stylolites and other diagenetic products at multiple scales. Using the well-known Lower Cretaceous Benic`assim case study area (Maestrat Basin, E. Spain), we provide new field and petrographic observations of how bedding-parallel stylolites can influence different diagenetic processes during basin evolution. The results reveal that stylolites can serve as baffles or inhibitors for different carbonate diagenetic reactions, and act as fronts for dolomitization, dolomite recrystallization and dolomite calcitization processes. Anastomosing stylolites that pre-date burial dolomitization probably acted as a collective baffle for dolomitization fluids in the study area, resulting in stratabound replacement geometries at the metre-to-kilometre scale. The dolomitization front coincides with stylolites, and can be traced along consecutive anastomosing ones. Such anastomosing stylolites are typical of mud-dominated facies that characterize limestone-dolostone transition zones. Conversely, dolostone bodies tend to correspond to more grain-dominated facies characterized by parallel (non-anastomosing) stylolites. Stylolites subsequently acted as fluid flow conduits and barriers when the burial and stress conditions changed. Stylolitic porosity enhanced by dissolution within dolostones close to faults appears filled with saddle dolomite riming the stylolite pore, and high-temperature blocky calcite cements filling the remaining porosity. The fluids responsible for these reactions were likely released from below at high pressure, causing hydraulic brecciation, and were channelised through stylolites, which acted as fluid conduits. Stylolites are also found acting as baffles for subsequent dolomite calcitization reactions during meteoric diagenesis and occasionally appear filled with iron oxides likely released by calcitization. This example demonstrates how the same type of stylolites (bedding-parallel) can act as barriers/inhibitors and/or conduits for different types of diagenetic reactions through time, and how important it is to consider their collective role when they form networks.
CRIS-Team WoS Importer:2022-02-11

Superimposed structures, incremental strain and deformation path from field data to modelling: A case study from the Alpi Apuane metamorphic core complex (NW Tuscany, Italy). - Molli, G.; Köhn, Daniel; Allacorta, L.; Danese, L.; Zampelli, S.; Zazzeri, M. (Journal of Structural Geology, 2022)
In this study, superimposed folds and antitaxial strain fringes are investigated to unravel the deformation path of the core zones of the Alpi Apuane metamorphic complex (northwest Tuscany Italy). Detailed field mapping combined with microstructural analyses is used together with computer-modelling of a complex strain fringe system to disclose the main steps of the Alpi Apuane syn-metamorphic deformation history. A comparison between natural investigated fibres and those produced by paraffine wax experiments provides details of the relative core-object-fringe rotation allowing new insight on the growth kinematics of strain fringes. The results of our analyses show that our composite fringe system is characterized by a first set of fibres to be related with the main composite axial planar foliation of regional scale isoclinal non-cylindric folds. This first set of fibre fringes records a local non-coaxial strain with an absolute core-object rotation (relative to an external reference frame represented by the main foliation) of 140° and a calculated shear strain (γ) of about 4. The second set of fringes, developed after the tilting of the main foliation and the first fringe-set in a sub-vertical orientation, records a lower absolute rotation of the core-object (25°), a lower shear strain (γ) of about 1.4 and a coaxial strain associated with the vertical shortening. This part of the composite fringe system and the related structures may relate to the switch from the crustal scale contractional regime to the extensional one, which characterized the development of the inner northern Apennines orogen.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Alpi Apuane; Modelling incremental strain; Northern Apennines; Strain fringes; Superimposed folds; Tectonics

U-Pb dating of calcite veins reveals complex stress evolution and thrust sequence in the Bighorn Basin, Wyoming, USA - Beaudoin, Nicolas; Lacombe, Olivier; Roberts, Nick M.W.; Köhn, Daniel (Geology, 2019)
CRIS-Team Scopus Importer:2019-09-17

Using fractured outcrops to calculate permeability tensors: implications for geothermal fluid flow and the influence of seismic-scale faults - Smith, Ruaridh; Lesueur, Martin; Kelka, Ulrich; Poulet, Thomas; Köhn, Daniel (Geological Magazine, 2022)
Faulted and fractured systems form a critical component of fluid flow, especially within low-permeable reservoirs. Therefore, developing suitable methodologies for acquiring structural data and simulating flow through fractured media is vital to improve efficiency and reduce uncertainties in modelling the subsurface. Outcrop analogues provide excellent areas for the analysis and characterization of fractures within the reservoir rocks where subsurface data are limited. Variation in fracture arrangement, distribution and connectivity can be obtained from 2D fractured cliff sections and pavements. These sections can then be used for efficient discretization and homogenization techniques to obtain reliable predictions on permeability distributions in the geothermal reservoirs. Fracture network anisotropy in the Malm reservoir unit is assessed using detailed structural analysis and numerical homogenization of outcrop analogues from an open pit quarry within the Franconian Basin, Germany. Several events are recorded in the fracture networks from the Late Jurassic the Alpine Orogeny and are observed to be influenced by the Kulmbach Fault nearby with a reverse throw of 800 m. The fractured outcrops are digitized for fluid flow simulations and homogenization to determine the permeability tensors of the networks. The tensors show differences in fluid transport direction where fracture permeability is controlled by orientation compared to a constant value. As a result, it is observed that the orientation of the tensor is influenced by the Kulmbach Fault, and therefore faults within the reservoirs at depth should be considered as important controls on the fracture flow of the geothermal system.
CRIS-Team WoS Importer:2022-06-10
Keywords: natural fractures; geothermal; numerical modelling; fluid flow; outcrop; permeability tensors

Vertical stress history and paleoburial in foreland basins unravelled by stylolite roughness paleopiezometry: Insights from bedding-parallel stylolites in the Bighorn Basin, Wyoming, USA. - Beaudoin, Nicolas; Lacombe, Olivier; Köhn, Daniel; David, Marie Eléonore; Farrell, Natalie; Healy, David (Journal of Structural Geology, 2020)
We apply the stylolite roughness inversion technique on sedimentary, bedding-parallel stylolites hosted in the Paleozoic carbonates of the Bighorn and Madison formations cropping out in the Bighorn Basin, Wyoming, USA. The inversion technique applied to bedding-parallel stylolites allows determination of the absolute magnitude of the vertical stress experienced at the time dissolution stops along the pressure-solution planes. At the basin scale, reconstructed vertical stress magnitudes range from 19 ± 2 MPa to 35 ± 4 MPa in the Bighorn Fm, and from 12 ± 2 MPa to 37 ± 4 MPa in the Madison Fm. Once converted into depth and compared with up-to-date basin models of burial and contractional history, the dataset highlights that bedding-parallel stylolites accommodated compaction from ca. 220 Ma until ca. 90 Ma, i.e. until stress build-up related to the Sevier contraction made the maximum horizontal principal stress high enough to overcome the vertical principal stress. This study is key to illustrate how stylolites can be used to consistently access paleoburial and to unravel both stress evolution and timing in foreland settings, and indicates that pressure-solution remains active throughout the carbonate deposition history.
CRIS-Team Scopus Importer:2020-04-24

Zebra dolomites of the Spessart, Germany: implications for hydrothermal systems of the European Zechstein Basin - Kelka, Ulrich; Beaudoin, Nicolas E.; Lorenz, Joachim; Köhn, Daniel; Regenauer-Lieb, Klaus; Boyce, Adrian; Chung, Peter (International Journal of Earth Sciences, 2023)
Zebra dolomites have a distinctive texture and are a peculiar structural variety of dolostones often encountered in the vicinity of base metal deposits commonly in the Mississippi Valley-Type (MVT). We investigate origin and evolution of the zebra dolomites found in the region of the Spessart, northwestern Bavaria, Germany, through diagenetic and petrogenetic analysis using SEM, CL microscopy, O–C isotopes, and fluid inclusion micro-thermometry. Here, we aim to shed light on the nature of the fluids that altered the zebra dolomite of the Zechstein formation. We distinguish the geochemical signatures of two different fluid flow regimes post-dating texture formation, each characterized by specific homogenization temperatures and oxygen–carbon isotope ratios (Event 1: T h = 120 °C; δ 18 O fluids = [0 to 2‰]; Event 2; T h = 300 °C; δ 18 O fluids = 18‰). Comparison of these fluids and the associated mineralization with published regional fluid flow data support that the zebra dolomites in the Spessart most likely coincided with the Permian large-scale fluid flow event that occurred throughout the European Zechstein Basin. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-11-17
Keywords: Dedolomitization; Dolomitization; Hydrothermal systems; Spessart; Zebra dolomites